Agama dan Budaya - Riadus Solihah Solihah (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2019)
Rokat tase ’is part of the tradition of the Gebang Village community which is carried out for generations. Rokat Tase 'is carried out every year by the people of Gebang Village as an effort to maintain tradition. Gradually, the implementation of this tradition underwent changes in line with changes in the socio-religious conditions of the people of Gebang Village. In the tradition of rokat tase ', this change is seen, for example, from a series of processions that have nuanced animism-dynamism into a series of Islamic traditions. This happened along with the strengthening of Islamic values ​​in the Gebang Village community. Strengthening Islamic religious values ​​has an influence on the series of implementation of the Rokat tase tradition. At present, the tradition of the Rokat Tase 'in Gebang Village already contains and contains Islamic values. Among them are the recitation of the tahlil, the recitation of the prayer of the Prophet and the reading of prayers offered to Allah SWT. This is far different from the initial conditions of the implementation of the Rokat tase tradition, which was originally nuanced with animism-dynamism.